His to take eaudiobook - Black, Shayla (Wicked Lovers, 2015)
Racing against time, NSA agent Joaquin Muñoz is searching for a little girl who vanished twenty years ago with a dangerous secret. Since Bailey Benson fits the profile, Joaquin abducts the beauty and whisks her to the safety of Club Dominion before anyone can silence her for good. At first, Bailey is terrified, but when her kidnapper demands information about her past, she's stunned. Are her horrific visions actually distant memories that imperil all she holds dear? Confined in a place that echoes with moans and breathes passion, Bailey finds that Joaquin is a fierce protector as well as a sensual Master. But giving in to him might be the most delicious danger of all because Bailey soon learns that Joaquin has a secret of his own. The exposed truth leaves her vulnerable and wondering how much about the man she loves is a lie and how much more is at risk than her heart. Contains mature themes.